IMPLEMENTASI FINTECH PADA LEMBAGA KEUANGAN SYARIAH DI KABUPATEN TEGAL DALAM MENINGKATKA KEUANGAN INKLUSIF - Mursekha; Lutfi Nawa Salsabil (JOURNAL ISLAMIC ECONOMICS AD DIWAN, 2025)
This study was conducted to determine how the implementation of financial technology (fintech) in Islamic financial institutions in increasing financial inclusion. The approach used in this study is a qualitative field research method. Data collection techniques in this study use data triangulation including documentation, interviews, and observations, data analysis used is by applying thematic analysis, which consists of three main stages, namely data reduction by selecting and organizing data based on main categories, data presentation. Based on field data, the results obtained that several LKS have developed Islamic mobile banking applications, digital payment systems, and online financing services based on Islamic contracts such as murabahah and ijarah, fintech has been proven to be able to increase public access to Islamic financial services, especially for unbanked and underbanked community groups. In its implementation, the Financial Institutions (LKS) in Tegal Regency stated that they adhere to Sharia principles through the supervision of the Sharia Supervisory Board (DPS). Challenges faced by LKS in implementing fintech include limited technological infrastructure in rural areas and low digital literacy among the public. Fintech implementation has had a positive impact on LKS performance, particularly in terms of increasing the number of customers, operational efficiency, and ease of service access. The active role of the DPS is also key to ensuring that the digital transformation remains within Sharia principles and has a broad impact on equitable financial inclusion.